Pengetahuan Ibu Hamil tentang Tanda Bahaya Kehamilan dan Kepatuhan Antenatal Care (ANC) - Suhartatik Suhartatik; Rusni Mato; Kartika Sari Wijayaningsih; Sitti Nurbaya; Ernawati Ernawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze pregnant women's knowledge of pregnancy danger signs and their compliance with Antenatal Care (ANC) visits. The study employed a quantitative approach using a cross-sectional design. The results showed that 34 respondents (70.8%) had good knowledge of pregnancy danger signs, while 39 respondents (81.2%) were compliant with ANC visits. The Chi-Square test yielded a p-value of 0.012 (p < 0.05), indicating a statistically significant association between pregnant women's knowledge of pregnancy danger signs and compliance with ANC visits. In conclusion, pregnant women with better knowledge of pregnancy danger signs tend to demonstrate higher compliance with Antenatal Care (ANC) visits. Keywords: Antenatal Care, Compliance, Knowledge, Pregnancy Danger Signs, Pregnant Women